Mobile Application System For Point of Sales in Coffee Sales at Langit Coffee Space - Yusril Aziz (INOVTEK Polbeng - Seri Informatika, 2024)
The coffee shop industry in Indonesia is experiencing rapid growth, leading to intense competition among businesses. Langit Coffee Space faces challenges in managing stock and financial reporting, which are still handled manually, resulting in frequent errors and difficulties in storing and retrieving increasing amounts of data. This study aims to develop a mobile-based Point of Sale (POS) application tailored for Langit Coffee Space to improve operational efficiency. Using the Extreme Programming methodology, the application integrates features for real-time stock management, digital ordering, automated financial reporting, and support for multiple payment methods, including digital payments. Testing results indicate that the application successfully reduced stock recording errors by 30% and shortened the time required to prepare financial reports by up to 50%, significantly enhancing efficiency. Compared to other solutions, this application provides flexibility for future feature enhancements, such as loyalty programs, which may not be available in general POS applications.